Comparison between Up-Conversion Detection in Glow-Discharge Detectors and the Schottky Diode for MMW/THz High-Power Single Pulse - Adnan Haj Yahya (Applied Sciences, 2021)
Generally, glow-discharge detectors (GDD), acting on miniature neon indicator lamps, and Schottky diode detectors serve as efficient, fast, and room-temperature millimeter wave (MMW)/THz detectors. Previous studies on GDD implemented a repetition of terahertz sources, and low-power radiation, and showed good results in terms of detection, responsivity, and noise-equivalent power. This paper presents a comparison between a detector based on a GDD lamp and a Schottky diode detector for the detection of a high-power single pulse. With this comparison, we touch upon two GDD detection methods, the visual light emitting from the GDD and the electrical current of the GDD detector. Results showed better response time and better sensitivity for the GDD detection method compared to with the Schottky diode.